A New Enhanced Microstrip Patch Antenna with Circular Polarization for mobile applications - Ait Lahcen Abdelilah; Chabaa Samira; Ibnyaich Saida; Zeroual Abdelouhab (ITM Web of Conferences)
This study shows an enhanced octagonal circularly polarized (CP) patch antenna, This one appropriate for mobile applications, such as wireless applications, especially for WIMAX, and 5G mid-band. A single-port excitation approach is utilized to obtain the intended outcome. The substrate used is Rogers RT/duroid 5880 with a relative permittivity of 2.2 and a low loss tangent (0.0009). The antenna’s dimensions are optimized with the final design measuring 32 × 35 × 1.67 mm3. To generate the circular polarization a square slot is cuted, and two stubs are inserted in the opposite corners of the ground plane. A good result is achieved, for the reflection coefficient, we have a bandwidth (< -10 dB) of 1.29 GHz (2.8 GHz-4.09 GHz) and the bandwidth of the Axial ratio (AR) below 3 dB is 500 MHz (3.33 GHz−3.83 GHz). (CST) and (HFSS) softwares were used to calculate all obtained results. This microstrip antenna has a tiny dimension, it is simple to fabricate and has a lightweight, it has high performance, such as a wide band of the reflection coefficient of 1.29 GHz, also, its circular polarization makes it ideal for mobile applications, particularly WIMAX and 5G mid-band.